Between Enforcement and Compliance: Navigating Regulatory Gaps and Local Realities in the Governance of Mini Trawl Fishing in West Aceh’s Coastal Waters - Aditya Riski Indra Pratama (Universitas Teuku Umar, 2026)
This study examines the institutional strategies and challenges in supervising the use of mini trawl fishing gear in West Aceh, Indonesia. Despite the existence of regulatory frameworks banning mini trawls due to their destructive ecological impact, enforcement remains inconsistent and fragmented. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving key agencies such as the Marine and Fisheries Office (DKP), Satwas SDKP, Water Police, and Navy. The findings reveal that institutional coordination is weak, with overlapping roles, limited patrol resources, and inadequate personnel training, all of which hinder effective supervision. Enforcement efforts vary across institutions, ranging from education-based approaches to legal prosecution. However, community compliance remains low due to economic dependency on mini trawls, lack of alternative livelihoods, and minimal engagement in regulatory processes. This gap between enforcement and compliance reflects broader regulatory and governance challenges. The study concludes that improving supervision effectiveness requires integrated inter-agency collaboration, enhanced field capacity, community-based monitoring, and policy approaches that balance ecological sustainability with socioeconomic realities. These findings contribute to the discourse on sustainable fisheries governance in Indonesia and offer practical insights for policymakers and local institutions to improve marine resource protection at the community level.